Playing SAFMEDS and Its Influence on the Vocabulary Learning of Hotel Department Students - Hardianti Hardianti; Haryanto Atmowardoyo; Kisman Salija (Universitas Negeri Makassar, 2018)
Playing Say All Fast Minute Every Day Shuffled (SAFMEDS), a set of cards containing details in both sides of the cards, has successfully helped many training of fluency and vocabulary development abroad (Quigley (2004); Kubina, Yurich, Durica, & Healy (2015); Beverly, Huge, & Hastings (2016)). However, none of them conducted their researches in the context of vocative education, and focused on English as a Foreign Language (EFL) or English for Specific Purposes (ESP). Thus, by intentionally opening the chance of adapting and transforming SAFMEDS to be applied in vocational high school classroom, the researcher conducted this study to find out whether or not there was any significant difference between the use of SAFMEDS and wordlist in vocabulary learning of two hotel department classrooms, and what are the aspects of vocabulary that might be highly influenced by SAFMEDS itself. This study was conducted purposively in the second grade of hotel department of SMK Negeri 3 Luwuk in the first term of 2017/2018 academic year. An English vocabulary test was administered to collect quantitative data by focusing on playing SAFMEDS containing hotel department terminologies as the core material. Through quasi-experimental research design, the analysis of quantitative data showed that there was a significant difference between the mean score of the students who were learning vocabulary by using SAFMEDS and the mean score of the students who were learning vocabulary by using wordlist. As for the second research question, the researcher found that the aspect of vocabulary which was dominantly affected by the use of SAFMEDS was the aspect of vocabulary in term of form.